Aging of the population and the quality of life - Gardocka-Jałowiec, Anna; Szalonka, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The paper aims at presenting the quality of life in terms of the deepening population aging process conditioned (to a great extent) by the progressive convergence of technologies. The interdisciplinary, theoretical nature of the considerations is a voice in the discussion on the interpretation, place, and role of quality of life, with particular emphasis on the extension of human life as a consequence of medical development.The authors applied the descriptive analysis method to present the category of quality of life, the phenomenon of population aging, the specificity of technological changes, and selected issues in the field of demographic changes. Polish and foreign literature on the subject was the basis for the considerations. The theoretical aspect of the research is supplemented by the empirical part supported by available secondary data published by Eurostat and Statistics Poland (Główny Urząd Statystyczny). Poland has been in the top thirty demographically old countries in the world for many years. In 1967, it crossed the threshold of demographic old age, and in 1980 — the threshold of advanced demographic old age. The demographic forecasts of Statistics Poland indicate that the number of people in retirement age will increase, and in 2035, it will reach 26.7% of the population. The observed and forecasted decline in the total population and the growth in the number of people in the senior age lead to an increase in the demographic dependency ratio of the elderly. The convergence of technologies revealed in medicine creates a new perspective on the population aging process. Extending human life allows one to recognize that the quality of life becomes: 1. the most desirable result of all healthcare policies; 2. dependent on the change of the healthcare model, i.e., the transition from the dominant model of reactive and retrospective care to the desired proactive and prospective model.
Keywords: quality of life; population aging; time; health; demographic changes; medical progress; technological change